A nexus between regional welfare and sustainable development: A conceptual model - Mariya V. Shlyapina; Elena A. Tretyakova (Journal of New Economy)
The relevance of the research stems from the nature of the approaches to the definition and measurement of regional welfare still debated in the extant research. Particular importance attached to this problem is related to the concept of sustainable development, which centres on promoting prosperity while protecting the planet. The paper aims to form an original theoretical model depicting the mutual influence of sustainable regional development and regional welfare. The fundamental propositions of the concept of sustainable development and welfare economics, as well as regional and spatial development theories constitute the methodological basis of the study. The methods used are comparative analysis, synthesis, and conceptual modelling. The findings confirm that regional welfare acts simultaneously as a target due to having the elements identical to the spheres of sustainable development in its struc ture, and as the key factor in the sustainable regional development due to incorporat ing a set of material and non-material, economic and non-economic goods, which build up the economic, social, environmental, and institutional elements ensuring an incessant process of changes in the regional socio-ecological-economic system impacted by interregional, national and international factors of external environment of a region. The proposed conceptual model advances scientific ideas about the main tenance of sustainable regional development, contributes to the theory of welfare, and creates a basis for devising a method to measure regional welfare.